2019
DOI: 10.1002/cbin.11282
|View full text |Cite
|
Sign up to set email alerts
|

RIPK4 suppresses the TGF‐β1 signaling pathway in HaCaT cells

Abstract: Receptor‐interacting serine/threonine kinase 4 (RIPK4) and transforming growth factor‐β 1 (TGF‐β1) play critical roles in the development and maintenance of the epidermis. A negative correlation between the expression patterns of RIPK4 and TGF‐β signaling during epidermal homeostasis‐related events and suppression of RIPK4 expression by TGF‐β1 in keratinocyte cell lines suggest the presence of a negative regulatory loop between the two factors. So far, RIPK4 has been shown to regulate nuclear factor‐κB (NF‐κB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
(82 reference statements)
0
8
0
Order By: Relevance
“…As previously reported, RIPK4, activates the NF‐κB and Wnt/β‐catenin signaling pathways, while suppressing the TGF‐β1/Smad signaling pathway (Dinçer et al, 2020; Huang et al, 2013; Meylan et al, 2002). Therefore, we performed the NF‐κB, Wnt/β‐catenin, and TGF‐β1/Smad‐regulated luciferase reporter assays to analyze the impact of p.Asp161His (D161H) substitution on RIPK4 kinase activity in those pathways.…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…As previously reported, RIPK4, activates the NF‐κB and Wnt/β‐catenin signaling pathways, while suppressing the TGF‐β1/Smad signaling pathway (Dinçer et al, 2020; Huang et al, 2013; Meylan et al, 2002). Therefore, we performed the NF‐κB, Wnt/β‐catenin, and TGF‐β1/Smad‐regulated luciferase reporter assays to analyze the impact of p.Asp161His (D161H) substitution on RIPK4 kinase activity in those pathways.…”
Section: Resultsmentioning
confidence: 53%
“…Previously, it was demonstrated that RIPK4, but not kinase inactive variants, directly activates PKC, Wnt/β‐catenin, and NF‐κB signaling similar to that caused by ligands of these pathways (Huang et al, 2013; Kwa et al, 2014; Meylan et al, 2002). In addition to these findings, our recent study revealed for the first time that, instead of being an inducer, the RIPK4 acts as a negative regulator in TGF‐β1/Smad signaling pathway (Dinçer et al, 2020). Therefore, NF‐κB, Wnt/ β‐catenin, and TGF‐β1/Smad signaling pathways were selected in order to analyze the impact of identified p.Asp161His variant on RIPK4‐regulated signaling events.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…•EGF [11,12] •Pep19-2.5 [13] •Hepatocyte Growth Factor (HGF) [14] •micro RNA 21 [15] •ERBB2 [16] •Keratinocyte Growth Factor (KGF) [17] •AES16-2M (ERK activating peptide) [18] •GFP-Smad2 [19] •Lipofectamine and KGF-mRNA [17] •SIS3 (Smad3 phosphorylation specific inhibitor) [19] •Liraglutide, a Glucagon-like peptide-1 analogue (concentration dependent) [20] •Thrombin [21] •AHR siRNA [22] •EGF receptor inhibitor (EGFRi) [19] •JNK inhibitor (JNKi) [19] •MEK1 inhibitor (MEKi) [19] •Enhanced green fluorescent protein (eGFP) with Lipofectamine [17] •LY 294002 (PI3K inhibitor) [20] •IDR-1018, a synthetic innate defense regulator peptide, in normoxia [23] •EGFR antagonist (AG1478) [21] •ERK1/2 antagonist (UO126) [21] •AHR antagonist, CH223191 [22] •RIPK4 via TGFβ [24] •ERBB3 [16] •ERK inhibitor (U0126) [18] •IDR-1018 in hypoxic condition [23] •ALK5 (TGF-ß receptor I) inhibitor (TGFRi) [19] •Cytochalasin D [22] •PXR siRNA [22] •PXR antagonist, SPA70 [22] •JNK inhibitor (SP600125 and indirubin) [22] Natural Products…”
Section: Decrease No Impactmentioning
confidence: 99%